Identifying differentially expressed genes under heat stress and developing molecular markers in orchardgrass (Dactylis glomerata L.) through transcriptome analysis. (7th May 2015) - Huang, L. K.; Yan, H. D.; Zhao, X. X.; Zhang, X. Q.; Wang, J.; Frazier, T.; Yin, G.; Huang, X.; Yan, D. F.; Zang, W. J.; Ma, X.; Peng, Y.; et al.
Abstract Orchardgrass (Dactylis glomerata L.) is a long‐lived, cool‐season forage grass that is commonly used for hay production. Despite its economic importance, orchardgrass genome remains relatively unexplored. In this study, we used Illumina RNA sequencing to identify gene‐associated molecular markers, including simple sequence repeats (SSRs) and single nucleotide polymorphisms (SNPs), as well as heat stress‐induced differentially expressed genes (DEGs) in two orchardgrass genotypes, 'Baoxing' (heat resistant) and '01998' (heat susceptible). Approximately 163 million high‐quality trimmed reads were generated from 207 million raw reads using the Illumina HiSeq 2000 platform. A total of 126 846 unigenes were obtained after de novo assembly of the trimmed reads, and 40 078 unigenes were identified as coding sequences (CDSs). Based on the assembled unigenes, 669 300 high‐quality SNPs, including 416 099 transitions and 257 736 transversions, were contained in 75 875 unigenes. In addition, a total of 8475 microsatellites were detected in 7764 unigenes. When placed under heat stress, the total number of DEGs in 'Baoxing' (3527) was higher than in '01998' (2649), indicating that in comparison with heat‐susceptible '01998', heat‐resistant 'Baoxing' seems to have more unigenes that respond to heat stress. The high‐throughput transcriptome sequencing of orchardgrass under heat stress provides useful information for gene identification and for the development of SNP and SSR molecular markers. The comparison of DEGs under different periods of heat stress allowed us to identify a wealth of candidate DEGs that can be further analysed in order to determine the genetic mechanisms underlying heat tolerance in orchardgrass.